The Development Of Early Childhood Creativity Through Yoga Asana - Harliana . (Universitas Muhammadiyah Ponorogo, 2020)
This research aims to describe and analyze the development of early childhood creativity through yoga asanaat PAUD Bali Public School Denpasar. Research uses qualitative case studies. Research data is taken through observations, in-depth interviews and documentation studies. The results of the analysis showed that there was a significant increase in the creativity of the students' imagination, while attending yoga asana activities packed in the form of games and also storytelling. Increased creativity can be seen after the child performs regular yoga asana for three up to six months. This can be seen from children's activities during learning activities both inside and outside the classroom.